EVALUASI KINERJA SUPPLIER MATERIAL UTAMA MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Nurwahyuni Anggita Marselina; Renanda Nia Rachmadita; Devina Puspita Sari (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
In the process of making fiberglass boats, there are many suppliers who supply the main materials for boats, one of which is CSM. Selection and evaluation of key material suppliers is one of the most important supply chain activities. In the process of selecting and evaluating suppliers, shipbuilding companies in Sidoarjo are often oriented towards the lowest price and this causes problems such as delays in material delivery. These problems can cause major losses for shipyards. This research aims to analyze the weight values of criteria, subcriteria and alternative suppliers so that companies can obtain the best Chopped Strand Mat (CSM) supplier who can provide the components needed by the shipyard. This research uses the AHP method to determine criteria, sub-criteria and alternative suppliers that comply with company standards. Based on the results of weighting between criteria, the highest weight for the quality criteria was obtained at 0.475 and from the results of weighting between subcriteria, the highest weight for the product specification sub-criteria was 0.208. Based on the results of the performance evaluation between suppliers, it was found that the KKT07FBG supplier was the best supplier with a weight of 0.110.